2012
DOI: 10.1074/jbc.m112.370544
|View full text |Cite
|
Sign up to set email alerts
|

The Rab Interacting Lysosomal Protein (RILP) Homology Domain Functions as a Novel Effector Domain for Small GTPase Rab36

Abstract: Background: Rab36 is an uncharacterized small GTPase that is largely conserved in vertebrates. Results: RILP family members and JIP3/4 contain a conserved RILP homology domain (RHD) that functions as an effector domain of Rab36. Conclusion: RILP functions as a Rab36 effector that mediates retrograde melanosome transport in melanocytes. Significance: Rab36 may regulate movements of Rab36-bearing vesicles/organelles through interaction with RHD-containing proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 44 publications
4
75
1
Order By: Relevance
“…Consistent with 56, we were unable to detect Rab36 expression in HeLa and so we focused on Rab7 and Rab34. Under normal growth conditions, expression of GFP‐Rab34 promoted the robust peri‐nuclear accumulation of lysosomes compared to expression of GFP alone, whereas expression of GFP‐Rab7 had no significant effect (Fig 3A).…”
Section: Resultssupporting
confidence: 56%
“…Consistent with 56, we were unable to detect Rab36 expression in HeLa and so we focused on Rab7 and Rab34. Under normal growth conditions, expression of GFP‐Rab34 promoted the robust peri‐nuclear accumulation of lysosomes compared to expression of GFP alone, whereas expression of GFP‐Rab7 had no significant effect (Fig 3A).…”
Section: Resultssupporting
confidence: 56%
“…This surface in SD-1 is thus an isoform-specific interaction site. Interestingly, it has been shown that this region of Myo5A is involved in binding to the isoform-specific adaptor RILPL2 (15) that binds to Rab36 (16).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, RILP also binds the tethering HOPS complex, thus coupling membrane tethering to microtubule minus-end transport (van der Kant et al 2013). RILP is also an effector of Rab36 that regulates retrograde melanosome transport in melanocytes (Matsui et al 2012), indicating that effectors can be shared between different Rab proteins localized to distinct intracellular compartments. Rab9 interaction with a Golgi-tethering factor, GCC185, promotes interaction with Rab6, Arl1, and the CLASP microtubule-anchoring protein and is suggested to integrate dynein-mediated delivery with docking of endosome-derived vesicles to the Golgi (Hayes et al 2009).…”
Section: Rab Gtpases and Microtubule-dependent Translocationmentioning
confidence: 99%